KNOWLEDGE, ATTITUDES AND PRACTICES TOWARDS OPEN EDUCATIONAL RESOURCES IN HIGHER EDUCATION INSTITUTIONS IN THE PHILIPPINES - Liezel G. Mohillo; Angie R. Jalandoon; Dave E. Marcial (Інформаційні технології і засоби навчання)
Open educational resources (OER) are well-known around the world and globally it gives revenue to Higher Education Institutions (HEIs). It also gives benefits in various Asian countries. However, in the Philippines there is a lack of information and implementation. With the update in education and the shift in learning modality a great need for educational resources - free and open to the public increases, especially in the outrage of the pandemic. These events and phenomena also create a schism between librarians' perspectives and practices on OER. This paper examines the academic librarians' knowledge, attitudes, and practices (KAP) toward OER in higher education institutions in the Philippines. Specifically, this paper is aimed at assessing the level of KAP toward OER among the librarians. It also investigates the relationship between KAP-OER and the profiles of academic librarians and libraries, as well as the differences between KAP-OER and sex, higher educational attainment, and years of service. The respondents of the study were the 57 academic librarians from different HEIs in the Philippines. An adapted questionnaire was used, and it was administered online through Google forms. Results show that academic librarians reinforce the trend of infrequent engagement in OER practices at the school. In terms of reuse, revise, remix, and redistribution, the respondents express a tendency to rarely engage in these practices at our school, with mean scores ranging from 5.31 to 5.75. On the general aspects of OER, the respondents exhibit a positive attitude, with a mean score of 5.27. The respondents and library profiles record no relationship to KAP. In contrast, print and nonprint resources can positively affect KAP. While sexes, highest educational attainment, and number of years of service shows no difference. This study concludes that Philippine academic librarians challenged in terms of KAP-OER. Thus, require the interventions for improvement. This study confirms that more research is needed. It suggests providing OER seminars and training, promoting OER through collaboration, funding, institutional incentives, and support for OER activities.